Optimization of friction stir processing parameters of aluminum alloy reinforced with hybrid nanoparticles using the Taguchi method - Ali, Mohammed Sultan; Saffar, Iman Q. Al (Zielona Góra: Uniwersytet Zielonogórski)
This study deals with the selection of optimum parameters for friction stir processing of Al alloy 6061-T6 reinforced with a hybrid nanoparticle (B4C and SiO2) in terms of their effect on the mechanical properties (hardness, tensile strength, and wear resistance) using Taguchi method. This work was carried out under four parameters each one running in three levels; rotational speeds (800, 1000 and 1200) rpm, travel speeds (10, 20, and 30) mm/min, holes depth (2, 2.5, and 3) mm, and mixing ratio of (SiO2/B4C) nanoparticles (1/1, 1/2, and 1/3), using L9 (34) Taguchi orthogonal array.
Keywords: aluminum alloy; friction stir processing; nanoparticles; Taguchi method; ANOVA